2020
DOI: 10.1103/physrevb.102.115162
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic exchange interactions in CrX3 ( X=Cl , Br, I) monolayers

Abstract: It has been predicted theoretically and indirectly confirmed experimentally that single-layer CrX 3 (X = Cl, Br, I) might be the prototypes of topological magnetic insulators (TMI). In this work, by using first-principles calculations combined with atomistic spin dynamics, we provide a complete picture of the magnetic interactions and magnetic excitations in CrX 3. The focus is here on the two most important aspects for the actual realization of TMI, namely the relativistic magnetic interactions and the finite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 93 publications
6
60
1
Order By: Relevance
“…In conclusion, we have demonstrated that an ab initio description of electron correlations beyond DFT can accurately describe the SW spectra and the stacking-dependent magnetism in a parameter-free fashion, and reveals the gap-opening mechanism in CrI 3 . An unexpected correlation-enhanced interlayer super-superexchange induces a gap along the Γ-K-M path in the absence of previously proposed relativistic exchanges or magnon-phonon interactions 23 . To experimentally verify the true physical mechanism of the gap opening and the nature of magnetic interactions, future INS experiments may be used to search for the bandcrossings off the high-symmetry line in bulk CrI 3 .…”
Section: Stacking-dependent Magnetic Orderingmentioning
confidence: 68%
See 3 more Smart Citations
“…In conclusion, we have demonstrated that an ab initio description of electron correlations beyond DFT can accurately describe the SW spectra and the stacking-dependent magnetism in a parameter-free fashion, and reveals the gap-opening mechanism in CrI 3 . An unexpected correlation-enhanced interlayer super-superexchange induces a gap along the Γ-K-M path in the absence of previously proposed relativistic exchanges or magnon-phonon interactions 23 . To experimentally verify the true physical mechanism of the gap opening and the nature of magnetic interactions, future INS experiments may be used to search for the bandcrossings off the high-symmetry line in bulk CrI 3 .…”
Section: Stacking-dependent Magnetic Orderingmentioning
confidence: 68%
“…By far, except for a few studies 23,38,39 using the magnetic force theorem (MFT) 40 , most of the theoretical investigations of the magnetic interactions in m2Dv are based on mapping the total energies of various collinear spin configurations into the Heisenberg model (referred to hereafter as the energy-mapping method), often employed with DFT + U. However, the applicability and accuracy of such an approach in CrI 3 are not clear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CrX 3 is a 2D FM insulator with FM originating from the Cr-X-Cr superexchange interaction [13,[23][24][25]. Six Cr 3+ ions * swagata.acharya@ru.nl form a honeycomb structure with D 3d point group symmetry, and each Cr is surrounded by six X in an octahedral geometry (see Fig.…”
Section: Introductionmentioning
confidence: 99%